Performance of computed tomography in diagnosis and evaluation of traumatic intracerebral hemorrhage - Hamood, Haider Q.; Hamood, Haider Q. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: The intracerebral hemorrhage (ICH) can be classified as traumatic and spontaneous. The frontal and temporal lobes are classic sites for traumatic ICH, which are less commonly affected by spontaneous episodes. Computed tomography (CT) scanning is the most accurate radiological method for demonstrating the acute lesion of intracerebral hemorrhage (ICH). Both types are of high density, but traumatic bleeding is more frequently multifocal, in this study we are dealing with traumatic type of intracerebral hematoma. Aim of the study is to identify the accuracy and performance of CT scan in diagnosis and evaluation of intracerebral hemorrhage. Patients and methods: 60 patients were examined, their ages range from 30-70 years with means age 48 years old, they were 36 males (60%), and 24 females (40%). Results: Our study reveals, the male patients (36 patients) were more affected than female patients (24 patients). Most affected age group in our study was 60-70 years old, 18 patients (30%) with no gender difference. Acute ICH was more than other ICH types, patients with acute ICH were 24 patients (40%) 15 male patients and 9 female patients, patients with subacute ICH were 20 patients (33%) and patients with chronic ICH were 16 patients (27%). In our study, the RTA was the most causative mechanism of ICH, 27 patients with RTA were seen in our study (45%), followed by shell injury which were 24 patients (40%) and then the fall from hight (FFH) which were 9 patients (15%). The most common CT feature noted in our study is the brain edema and it is seen in 27 patients (45%). Basal ganglia were most affected brain region (45%) of cases. Conclusion: CT is available, rapid imaging modality in the diagnosis of ICH, so it is suitable for diagnosis and evaluation of ICH as emergency cases in casualty department and it is valuable in evaluation of traumatic I.C.H. especially in acute stages.